Ragam Qiraat Al-Qur'an - Fathoni, Ahmad (SUHUF, 2009)
The object of the study of the knowledge of the variety of the Quranic reading is the Qur'an itself. The focus is on the difference of the reading and its articulation. The method is based on the riwayat or narration which is originated from the Prophet (Rasulullah saw) and its use is to be one of the instruments to keep the originality of the QurÃ¢â‚¬â„¢an. The validity of the reading the QurÃ¢â‚¬â„¢an is to be judged based on the valid chainÃ‚ (sanad Ã‚Â¡aÃ‚Â¥Ã„Â«Ã‚Â¥)Ã‚ in accord with the Rasm UÃ‚Â£mÃ„ÂnÃ„Â« as well as with theÃ‚ Arabic grammar. Whereas the qualification of its originality is divided into six stages as follow: the first is mutawÃ„Âtir, the second is masyhÃ…Â«r, the third is Ã„ÂhÃ„Âd, the fourth is syaz, the fifth is maudÃ…Â«Ã¢â‚¬Ëœ, and the six is mudraj. Of this six catagories, the readings which can be included in the catagory of mutawÃ„Âtir are Qiraat SabÃ¢â‚¬Ëœah (the seven readings) and Qiraat Ã¢â‚¬ËœAsyrahÃ‚ (the ten readings). To study this knowledge of reading the QurÃ¢â‚¬â„¢an (ilmu qiraat), one is advised to know about special terms being used such asÃ‚ qiraatÃ‚ (readings), riwayat (narration), tarÃ„Â«q (the way), wajh (aspect), mÃ„Â«m jamaÃ¢â‚¬Ëœ, sukÃ…Â«n mÃ„Â«m jamaÃ¢â‚¬Ëœ and many others.